Binary search algorithm for adaptive impedance matching network. Issue 9 (11th April 2016) - Xiong, B.; Hofmann, K.
Abstract : A novel design strategy for adaptive impedance matching network which consists of two tunable components is presented. The input resistance is controlled by the first tunable component and independent of the second tunable component. Additionally, the proposed strategies ensure that the input resistance is proportional to the first tunable component and input reactance is proportional to the second tunable component. Therefore, the binary search algorithm is employed to calibrate the tunable matching network. In contrast to the single‐step method, the convergence speed is improved from O ( N ) to O (log N ).